1994
DOI: 10.1002/ijc.2910580620
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated aluminium phthalocyanines as sensitizers for photochemotherapy. Effects of small light doses on localization, dye fluorescence and photosensitivity in V79 cells

Abstract: V79 cells incubated with di- or tetrasulfonated aluminium phthalocyanines (AlPcS2 or AlPcS4) showed a granular fluorescence pattern. Co-staining with the lysosomotropic dye acridine orange (AO) indicated that the granules that were stained by these photoactive phthalocyanines were identical to lysosomes. Small light exposures made the lysosomes permeable to the dyes without inactivating the cells. Also, the lysosomal enzymes beta-AGA and cathepsin (L+B) were inactivated by small light exposures when AlPcS4 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
3
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 29 publications
6
48
3
1
Order By: Relevance
“…Or, leaked lysosomal proteases might decrease mitochondrial transmembrane potential, as revealed in the present study by the cleavage of a Bcl-2 family member, Bid [46]. However, we could not rule out the possibility that PDT directly damaged mitochondria, inducing apoptosis, since lysosomal damage was not directly proved in the present study, and, as suggested by Moan et al [47], subcellular redistribution might occur during light activation. With ED 99 , two possibilities were considered.…”
Section: Discussioncontrasting
confidence: 44%
“…Or, leaked lysosomal proteases might decrease mitochondrial transmembrane potential, as revealed in the present study by the cleavage of a Bcl-2 family member, Bid [46]. However, we could not rule out the possibility that PDT directly damaged mitochondria, inducing apoptosis, since lysosomal damage was not directly proved in the present study, and, as suggested by Moan et al [47], subcellular redistribution might occur during light activation. With ED 99 , two possibilities were considered.…”
Section: Discussioncontrasting
confidence: 44%
“…Thus, it remains elusive whether redistribution, for example, to mitochondria, is essential for the high efficacy of the Si(sol) 2 Pc or if it is the result of disruption of the lipid droplet integrity, which itself could be responsible for inducing the observed photodynamic effect. Investigating the site of ROS formation [54][55][56] or determination of the activity of marker enzymes for specific organelles 57,58 after illumination of cells incubated with Si(sol) 2 Pc could be a valuable tool to elucidate this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in tumor type notwithstanding, some general structure/tumor accumulation trends can be seen. Amongst the tetraanionic sensitizers the highest % ID in the tumor was found for AIPcS, (6), while a tetracarboxyl porphyrin gave a maximal tumor concentration approximately half that of AIPcS, (6), but at twice the injected dose. The compound MACE (1).…”
Section: -$ Rz Rzmentioning
confidence: 99%
“…Rather, the nurnber of negative charges is the determining factor. The exact amount of negative charge that prevents diffusion across the cell membrane and allows endocytosis to become the dominant mode of entry seems to be around -2; however, the situation for AIPcS, (8) is confused by conflicting reports of lysosomal localization (6) and diffuse distribution throughout the cytoplasm (4). This situation is most likely a reflection of difficulties in purifying this compound.…”
mentioning
confidence: 99%